Managing Consultants. A practical guide for busy public sector managers - Dobes, Leo (ANU Press, 2016)
Public service cutbacks have increased reliance on consultants. But new legislation and rules governing the procurement of services from consultants are scattered over different legislative instruments. The first edition of this book attracted a record number of online hits. Busy public sector managers now have available to them an updated version that integrates an easy-to-follow, step-by-step guide that incorporates the many practical tips needed for successful procurement activity.